Bankruptcy Risk Mitigation: A Strategy for Analyzing Bank Health Based on RGEC Towards BPR Sustainability - Fitriyani, Yuniar; Dewi, Mariana Puspa (International Journal of Science and Society, 2025)
The purpose of this study is to investigate the effect of bank soundness, assessed using the RGEC framework (risk profile, good corporate governance, earnings, and capital), on the financial distress of rural credit banks in Malang Raya, utilizing financial reports from March 2024 through March 2025. All Rural Banks (BPRs) operating in the Greater Malang area were included as the population of this study. Using purposive sampling, the study sampled 17 BPRs in Greater Malang over a two-year period, resulting in 34 data sets. This mixed-methods study combined qualitative and quantitative approaches and was then analyzed using multiple regression analysis. The study reveals that financial distress is significantly affected by NPL, GCG, ROA, and CAR.